ANALISIS YURIDIS TERKAIT FUNGSI DAN KEWENANGAN DPD DALAM KETATANEGARAAN INDONESIA - Tifanni Tifanni (Fakultas Hukum Universitas Tarumanagara, 2021)
State institutions that emerged after the amendment to the 1945 Constitution were regulated in article 22 called the Regional Representative Council (DPD) with the aim that the regions have the right to participate in decision making and to accommodate the aspirations of the regional community, but there are problems in the functions and powers of the DPD which which is not in accordance with the initial purpose of forming the Regional Representative Council (DPD), this study aims to analyze the functions and authorities of the DPD after the amendment to the 1945 Constitution. This writing uses normative research, and also uses legal sources from books, laws and regulations and websites. This research shows that after the amendment to the 1945 Constitution the functions and powers of the DPD are very limited, therefore it should make changes related to the functions and authorities of the DPD in order to carry out their duties properly.